Conditional probability of graft survival in liver transplantation using donation after circulatory death grafts – a retrospective study. (13th July 2021) - Sasaki, Kazunari; Nair, Amit; Firl, Daniel J.; McVey, John C.; Moro, Amika; Diago Uso, Teresa; Fujiki, Masato; Aucejo, Federico N.; Quintini, Cristiano; Kwon, Choon‐Hyuck D.; Eghtesad, Bijan; Miller, Charles M.; et al.
Summary: The use of livers from donation after circulatory death (DCD) is historically characterized by increased rates of biliary complications and inferior short‐term graft survival (GS) compared to donation after brain death (DBD) allografts. This study aimed to evaluate the dynamic prognostic impact of DCD livers to reveal whether they remain an adverse factor even after patients survive a certain period following liver transplant (LT). This study used 74 961 LT patients including 4065 DCD LT in the scientific registry of transplant recipients from 2002–2017. The actual, 1 and 3‐year conditional hazard ratio (HR) of 1‐year GS in DCD LT were calculated using a conditional version of Cox regression model. The actual 1‐, 3‐, and 5‐year GS of DCD LT recipients were 83.3%, 73.3%, and 66.3%, which were significantly worse than those of DBD (all P < 0.01). Actual, 1‐, and 3‐year conditional HR of 1‐year GS in DCD compared to DBD livers were 1.87, 1.49, and 1.39, respectively. Graft loss analyses showed that those lost to biliary related complications were significantly higher in the DCD group even 3 years after LT. National registry data demonstrate the protracted higher risks inherent to DCD liver grafts in comparison to their DBD counterparts, despite survival through the early period after LT. These findings underscore the importance of judicious DCD graft selection at individual center level to minimize the risk of long‐term biliary complications.